Penerapan Model Make a Match Dalam Pembelajaran IPS di Sekolah Dasar - Sofiana Defi; Bahauddin Azmy; Dian Kusmaharti (PT. Media Edukasi Borneo, 2020)
This research is motivated by the selection of learning models that do not attract the attention of elementary school students and the amount of material that requires students to memorize it. This study aims to describe the implementation of the make a match model in the activities of educators and students in social studies learning and describe the learning outcomes of applying the make a match model. The research conducted was descriptive quantitative research. The population in this study were all grade 5 students. The sample used was all students of class V, amounting to 27 students. Data collection techniques in this study were observation and learning achievement tests. Data analysis techniques in this study using the percentage formula. Based on the results of research using the make a match learning model, it is known that the activities of educators are included in very good criteria, the activities of learners include very good criteria, and for completeness of learning outcomes get very good categories. ABSTRAK Penelitian ini dilatarbelakangi oleh pemilihan model pembelajaran yang kurang menarik perhatian peserta didik khususnya tingkat sekolah dasar (SD) serta banyaknya materi yang menuntut peserta didik untuk menghafalkannya. Penelitian ini bertujuan untuk mendeskripsikan keterlaksanaan model make a match pada aktivitas pendidik dan peserta didik dalam pembelajaran Ilmu Pengetahuan Sosial (IPS) serta mendeskripskan hasil belajar dari penerapan model make a match. Penelitian yang dilakukan ini adalah penelitian kuantitatif deskriptif. Populasi dalam penelitian ini adalah seluruh peserta didik kelas V. Sampel yang digunakan adalah seluruh peserta didik kelas V yang berjumlah 27 peserta didik. Teknik pengumpulan data dalam penelitian ini adalah observasi dan tes hasil belajar. Teknik analisis data yang dalam penelitian ini menggunakan rumus persentase. Berdasarkan hasil penelitian dengan menggunakan model pembelajaran make a match diketahui bahwa aktivitas pendidik termasuk kriteria sangat baik, aktivitas peserta didik termasuk kriteria samgat baik, serta untuk ketuntasan hasil belajar mendapatkan kategori sangat baik. KATA KUNCI: SD, model pembelajaran make a match, pembelajaran IPS.